Perspective Plan of Gujarat 1974-1984 Volume III - Planning Commission (Planning Commission, 1974)
Soon after the introduction of President’s Rule in Gujarat, the State Planning Advisory Board was reconstituted with the Governor as the Chairman, the Adviser to the Governor as the Vice-Chairman and with industrialists and experts in various fields of development as Members. In the first meeting of the reconstituted Board held on the 5th July 1971, it was decided to prepare a Perspective Plan for the economic development of the State for the decade 1974-84 with the basic objectives of full employment, more production, equitable distribution, diffusion of economic power and balanced development.
Report of the Working Group on Education and Manpower Planning